Analysis of Digital Literacy Learning Based on the Seven Alur MERDEKA Stages - Febi Dwi Widayanti; Eny Wahyu Suryanti; Sri Rahayuningsih; Khoirotul Bariyah (AL-ISHLAH: Jurnal Pendidikan, 2025)
This research analyzes the implementation of digital literacy learning based on the Seven Alur MERDEKA stages in several Madrasah (schools focusing on Islamic religious education) of Malang City. Kota Malang. Digital literacy is considered a crucial competency for preparing students to face the digital era, encompassing the ability to access, evaluate, and wisely use information through various technological platforms. Using a qualitative-descriptive approach, the research reveals that the learning model based on the Seven Alur MERDEKA stages—Mulai dari Diri, Eksplorasi Konsep, Ruang Kolaborasi, Demonstrasi Kontekstual, Elaborasi Pemahaman, Koneksi Antar Materi, and Aksi Nyata—is effective in improving student engagement, digital literacy comprehension, as well as their critical thinking and collaboration skills. The implementation results indicate that the initial stages, such as Starting from Self to Contextual Demonstration, were successfully applied with a success rate exceeding 80%. However, at the Real Action stage, only 55% of students fully carried out direct learning in their environments, highlighting the need for additional support to enhance student engagement in the practical application of digital literacy. Teachers received intensive training to implement this model, which also supported them in creating interactive and relevant learning experiences to student’s needs.  This research recommends adopting similar models in other schools to strengthen digital literacy and ensure students are better prepared for the challenges of the digital era. Furthermore, it emphasizes the importance of the teacher’s role in integrating digital literacy into the curriculum and encouraging students’ real actions as a form of sustainable learning implementation.